THE IMPORTANCE OF RISK ASSESSMENT IN CAPITAL ALLOCATION (American Journal of Interdisciplinary Research and Development, 2024)
Risk assessment in capital allocation in the management of the process of capital and financial provision, risk assessment in capital allocation plays a decisive role and ensures their use. Effective financing involves planning, forecasting and monitoring cash flows to maintain liquidity and meet financial obligations.